World development report, 1978-. (Oxford University Press, 1978)
The report "examines the relationship among competing policy objectives-reducing poverty, maintaining growth, improving social cohesion, and protecting the environment-over a 50-year horizon." The report is divided into nine chapters which deal with topics ranging from "Global Problems and Local Concerns" to "Getting the Best from Cities." While the casual reader may not have time to read the entire report, there is a 30-page overview that provides a description of the basic themes contained within the full report. At its essence, the report argues that "development is sustainable if the rules of the game are transparent and the game is inclusive." This important document will be especially relevant to those with an interest in sustainable development from an inclusive and global perspective. (Contents fro 2003 issue)